Bridging Social Capital pada Organisasi Kepemudaan Kingkilaban dalam Meningkatkan Perekonomian Masyarakat di Desa Balewangi, Kecamatan Cisurupan, Kabupaten Garut - Tresna, Sekar (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2023)
Bridging social capital is a form of social capital that enables the creation of both vertical relationships involving differences in status and position, and horizontal relationships involving the exchange of values and culture, leading to resource transfer. This study focuses on: 1) Relationships in the structural aspect encompassing vertical and horizontal bridging social capital, and 2) Relationships in the cognitive aspect concerning mutual trust between the Kingkilaban Youth Organization, the government of Balewangi Village, and community leaders, to understand how bridging social capital can enhance the community's economy. The study usedqualitative methods such as in-depth interviews, observations, and Venn diagram. The results of the research show that there are 6 factors that underlie bridging social capital that can be well established, namely: 1) value of usefulness, 2) similarity of goals, vision and hopes; 3) initiative and validation of existence, 4) division of roles according to abilities, 5) exchange of resources, and 6) active participation from each party can be fulfilled.. In the relationship with the government of Balewangi Village, two factors are lacking: expected role fulfillment and village government participation. Thus, addressing these aspects is essential for developing the relationship between The Kingkilaban Organization and the government of Balewangi Village. Pemuda Bergerak Desa Berdaya Program is designed to strengthen relationships through collaboration between the Kingkilaban Organization and the government of Balewangi Village. Keywords: Bridging Social Capital Relation, Structural Aspect, Cognitive Aspect